EKSISTENSI BAHASA INDONESIA DALAM BAHASA GAUL DI UNIVERSITAS VETERAN BANGUN NUSANTARA - Bintarawati, Niken; Wicaksana, Muhlis Fajar; Muryati, Sri (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
The Existence of Indonesian in Slang at Universitas Veteran Bangun Nusantara. This research aims to describe the use of slang compared to the existence of good and correct Indonesian language in university students. A qualitative descriptive method is applied in this research. There were 36 students from 11 study programs who were used as samples. The sampling technique used snow ball sampling technique. Data collection techniques used were observation, documentation, and questionnaires. Data analysis involves data collection, data reduction, data presentation, and conclusion drawing. The results obtained show that 66.7% of students use slang, and the remaining 33.7% often use good and correct Indonesian. The forms of slang used are abbreviations, translations, and puns.